TIME-TREND ANALYSIS OF DENGUE FEVER IN JAIPUR – A RECORD-BASED STUDY - Kukreja, Srishti; Sharma, Pankaj kumar; Sunda, Jagdish Kumar; meena, Sadhana; Baig, Vaseemnaheed (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Dengue is a vector-borne disease and is a major public health threat globally. The number of dengue cases reported to the World Health Organization increased over 8 fold over the past two decades, from 505,430 cases in 2000 to 5.2 million in 2019. The total number of cases seemingly decreased during years 2020 and 2021, as well as for reported deaths. However, the data are not yet complete and COVID-19 pandemic might have also inhibited case reporting in several countries. This record-based study was planned to study the annual and seasonal trend of dengue fever (DF) and effect of COVID-19 on reporting of DF. Methods: The record-based analysis was done by collecting data from the CMHO after taking informed consent from the Chief Medical and Health Officer, Jaipur. Data from the past 5 years (i.e., 2017–2021) were collected to study the annual and seasonal trends of dengue in Jaipur. Descriptive statistics was expressed in percentage and proportions. Data were entered in Microsoft Excel and analyzed using Epi info version 7.2.2.6 (software). Results: The number of cases increased from 2017 to 2018 with a slight decrease in 2019. There is sudden decrease in the number of cases from 2019 to 2020 which clearly shows the effect of COVID-19 pandemic. It was noticed that the number of cases starts increasing from August and reaches a peak in October and then starts decreasing. Conclusion: Dengue is present throughout the year but becomes a public health problem in the third quarter of year. Under-reporting of dengue cases and similar clinical presentation as COVID-19 made situation more difficult in its diagnosis and management that ultimately results in less cases reported in 2020.